PENGELOLAAN ALOKASI DANA DESA DALAM PEMBERDAYAAN MASYARAKAT - Sri Sapitri; Rinto Alexandro (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2021)
VillageFund Allocation Management in Community Empowerment. Village fund allocations are central and regional financial balance funds received by regencies / cities, which are distributed proportionally to each village in a proportion of at least 10% (ten percent). Allocation of village funds for village governance and community empowerment. This research uses a qualitative method using descriptive. The results showed that normative and governance of village allocation funds were carried out well, but the substance still did not meet the true meaning of empowerment. In addition, some stakeholders also have not played a maximum role, only the village head as the implementation team that manages the village allocation funds. The paternalistic community of the village community chooses the people who trust and support the village to manage village funds, as well as dominating the sub-district in making accountability letters that lead to increased village independence.